PERAN DAN KEDUDUKAN ILMU MATEMATIKA DALAM PENDIDIKAN PANCASILA - Rambe, Yuli Nirmaida (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This essay examines the relationship between mathematics and Pancasila Education in shaping students' character based on the nation's noble values. As a branch of science that emphasizes logic, precision, and consistency, mathematics is not only important academically but also plays a significant role in internalizing Pancasila values ​​such as justice, humanity, and wisdom. Pancasila Education aims to instill morality and national identity, which can be strengthened through a mathematical approach to decision-making and problem-solving. By integrating mathematics learning into the Pancasila values ​​framework, education becomes a strategic tool in developing rational, ethical, and responsible individuals